Heavy metal pollution status, spatial distribution and associated ecological risks within sediments of Yundang Lagoon catchment in Xiamen, China, after 30 years continuous ecological rehabilitation and management. Issue 2 (7th February 2021) - Uddin, Mohammad Mazbah; Xie, Bin; Peng, Guogan; Huang, Lingfeng
Abstract: This study aims to assess the pollution status and spatial distribution of heavy metals, including Chromium (Cr), Manganese (Mn), Nickel (Ni), Copper (Cu), Zinc (Zn), Arsenic (As), Cadmium (Cd), and Lead (Pb), in sediments from the Yundang Lagoon catchment, and to determine the risk from such metals and associated possible sources. Results show considerable spatial variations in total concentrations of heavy metals within sediment samples. The Geo-accumulation index indicates that sediment is not contaminated with Cr, Mn, Ni, and As, but moderate to high levels of Cu, Zn, Cd, and Pb are present. The potential ecological risk is low for Cr, Mn, Ni, Cu, Zn, As, and Pb, but Cd in lagoon sediments poses a considerable ecological risk to biota. A high positive correlation was found between Zn, Cu, and Cd ( r > 0.8), while Zn, Cd, and Cu ( r > 0.7) were positively correlated with total organic carbon. Principal component analysis indicated that Cr, Ni, Mn, and As was mainly from the lithogenic origin and Zn, Cu, Cd, and Pb were influenced by anthropogenic contamination. We identified evidence of point source and runoff are the main contributors to enhanced heavy metals levels.